A Multicenter Retrospective Study of 58 Patients With Primary Thyroid Diffuse Large B Cell Lymphoma - Yi, Jianing; Yi, Pingyong; Wang, Wei; Wang, Huan; Wang, Xinyu; Luo, Hanjia; Fan, Peizhi (Frontiers in Endocrinology, 2020)
Background: Primary thyroid diffuse large B cell lymphoma (DLBCL) is a rare type of extranodal lymphoma; optimal treatment methods and the key prognostic factors have not been established. Methods: The clinical data of 58 patients with primary thyroid DLBCL from January 2007 to December 2017 were collected. The Kaplan–Meier method and log-rank tests were used for the survival analysis. Cox regression analysis was performed to evaluate the prognostic factors. Results: The follow-up time was 6–120 months; 5-year overall survival (OS) and progression-free survival (PFS) were 73 and 61%, respectively. Single-factor analysis showed that IPI, Ki-67, treatment modalities, Hans classification, Myc/Bcl-2 protein co-expression, and administration of rituximab had a significant effect on the 5-year OS and PFS (P < 0.05), while age, sex, Bcl-2 protein expression, Myc protein expression, tumor stage, tumor size, Hashimoto's thyroiditis, and B symptoms were not associated with prognosis (P > 0.05). Multivariate risk regression analysis revealed that Myc/Bcl-2 protein co-expression, treatment modalities, and rituximab were independent prognostic factors (P < 0.05). Conclusions: Patients with primary thyroid DLBCL who received combination chemotherapy with radiotherapy had a better prognosis. Surgical treatment alone was not associated with the prognosis and is used only for diagnosis. Rituximab could improve the survival time of patients.